Development of Module Based on Higher Order Thinking Skills on Cylinder and Cone Matter - Indraswari, Nur Fitriyah; Raniati, Raniati; Aini, Kurratul (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2025)
This study aims to develop a valid, practical, and effective Higher Order Thinking Skills-based learning module on Cylinders and Cones for SMP NU Sumenep seventh-grade students. This type of research is research and development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected using tests and questionnaires. Material and media experts validated the results. The results of the study show: 1) the validity aspect obtained an average of 87.5% with the criteria of